Influence of calving age, parity, and calf gender on lactation metrics, reproductive and economic efficiency parameters in Egyptian buffaloes - El-Qaliouby, Hadeel S.; El-Kasrawy, Nagwa I.; Abouelghait, Hassaballah A.; Hegazy, Mohamed M.; Abd El-Aziz, Ayman H. (Journal of Advanced Veterinary Research, 2024)
Buffalo reproductive performance and sustained productivity measures remain inadequately studied. This study aimed to investigate the influences of calving age, parity, and calf gender on specific indicators, including days in milk (DIM), daily milk yield (DMY), total milk yield (TMY), and 270-days milk yield (270-DMY), alongside reproductive and economic parameters. Analyzing 2112 buffalo cow datasets from 1994-2022, acquired from five distinct farms associated with Egypt’s Animal Health Research Institute (AHRI) in Kafr El-Sheikh province, notable findings emerged. There was a marked influence of calving age and parity order on the milk yields, with buffaloes aged 8-10 years exhibiting peak yields. A significant uptrend was observed in milk yield metrics from the initial to the seventh parity. Notably, reproductive durations, including days open, calving intervals, and dry periods, peaked during the first parity. Economic evaluations revealed that first parity buffaloes recorded the least production expenditures. In contrast, seventh lactation buffaloes were the most profitable. A noteworthy observation was that buffalo calving less than six years demonstrated reduced production costs. Net profit showed the peak within the age of less than 6 to 8 years before tapering off. Contrarily, calf gender remained inconsequential across the studied parameters. The study highlights the importance of integrating production, reproductive, and economic determinants in buffalo breeding optimization strategies.